Dilemmas of the Sharing Economy in the Age of Access - Viegas da Costa-Nascimento, Daniela; dos Santos de Sousa Teodósio, Armindo; de Rezende Pinto, Marcelo (Organizações & Sociedade, 2021)
In the discussions involving the sharing economy, it is possible to see a tendency to highlight its positive aspects. However, the debates seem to neglect problematizations regarding the dilemmas and consequences of what sharing can mean for the social groups interested in embracing the sharing economy concept. In the age of access, the lack of ownership of goods may indicate a transformation concerning life in society. However, the essence of collaboration inherent in the sharing economy might be questioned, as the shared system would be just an attractive instrument with a friendly discourse mostly used to transfer the responsibility of the industry to the citizen, under the banner of mutual aid. Thus, our article seeks to investigate the different perspectives on sharing by analyzing its main dilemmas. Our study presents a critical view of the barriers, vulnerabilities and illusions present in this specific issue, which most studies and approaches on the subject end up reproducing. As a theoretical contribution to the literature, we point out that only those who have access to the sharing system are able to participate effectively, and their excesses reiterate the economicist and utilitarian structure based on inequality.